ABOUT THE ELECTROMAGNETIC COMPATIBILITY OF ELECTRICAL EQUIPMENT OF PASSENGER CARS - Raspopin, V. R.; Shapoval, O. V.; Snitko, L. Yu.; Ihnatov, H. S.; Vyslohuzov, V. T. (Science and Transport Progress, 2007)
The question of electromagnetic compatibility with signaling and communication devices of the electric equipment of domestic production coaches is surveyed; the problems rising before domestic rail car manufacturer in connection with providing of accomplishment of the normative documentation requirements on electromagnetic compatibility for the purpose of traffic safety rising of the rail rolling stock and providing the passengers safety during passenger traffic are stated.